Social professionals in school: a comparative study - Vieira, Ana (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
School education is progressively becoming a social question and not only a matter of pedagogic nature. The increase of the diversity of the audience present in the school has brought forth policies and differentiating school responses which aim to build a school for all. In this paper we seek to understand how the growing social tensions which are observed in the form of indiscipline at school are managed, whether towards other social professionals or only towards teachers. This paper presents a comparative study between three educational contexts which comprise socio-pedagogic mediation practices: Educational Context of Early Intervention (Terririo Educativo de Interveno Prioritria - TEIP) and two Support Offices for Students and their Families (Gabinetes de Apoio ao Aluno e Famlia - GAAF). In the three cases, there are senior social workers (tcnicos superiores de trabalho social - TSTS), social educators, youth workers and social assistants who work with teachers on a daily basis. The research done in this paper focuses mainly on the teachers opinion concerning the emergence of these new professions and their socio-pedagogic contribution in the school.